2017
DOI: 10.1080/23279095.2017.1323754
|View full text |Cite
|
Sign up to set email alerts
|

Variance in caregiver burden predicted by patient behaviors versus neuropsychological profile

Abstract: Informal caregivers provide the majority of care to persons with dementia; efforts to support caregivers' well-being are increasingly important in the context of limited formal healthcare supports. Informal caregiving is commonly associated with caregiver burden and burden may depend upon patient characteristics including neuropsychological profile, dementia severity, and dementia etiology. This study investigated predictors of caregiver burden in a sample of 213 Memory Clinic patients diagnosed with dementia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 35 publications
1
8
1
Order By: Relevance
“…This implies that although nurses agreed that these patients had impaired daily function, they did not see it as a source of stress. This is in contrast with previous studies with informal caregivers (Schoenmakers et al, 2010;Branger et al, 2017;Terum et al, 2017). Impaired daily function is associated with more functional dependence, likely resulting in more stress for family caregivers.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…This implies that although nurses agreed that these patients had impaired daily function, they did not see it as a source of stress. This is in contrast with previous studies with informal caregivers (Schoenmakers et al, 2010;Branger et al, 2017;Terum et al, 2017). Impaired daily function is associated with more functional dependence, likely resulting in more stress for family caregivers.…”
Section: Discussioncontrasting
confidence: 92%
“…Several studies have examined the factors affecting caregiver burden. While dementia severity, behavior disturbances, and impaired daily function have been found to be significant predictors in many studies (Schoenmakers et al, 2010;Song and Oh, 2015;Branger et al, 2017;Terum et al, 2017), cognitive function seems to be a controversial factor (Schoenmakers et al, 2010;Lee et al, 2013;Kucukguclu et al, 2017;Sinha et al, 2017). Age, female gender, and some neuropsychiatric symptoms (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the studies discussing dementia and caregiver burden are cross sectional (Huang et al, 2012 ; Yu et al, 2015 ; Hashimoto et al, 2017 ; Torrisi et al, 2017 ; Branger et al, 2018 ; Kawano et al, 2020 ; Lucijanić et al, 2020 ; Jhang et al, 2021 ; Tsai et al, 2021 ). Most of these articles supported that patient neuropsychiatric symptoms (Huang et al, 2012 ; Hashimoto et al, 2017 ; Torrisi et al, 2017 ; Branger et al, 2018 ; Kawano et al, 2020 ; Tsai et al, 2021 ), poor performance of activities for daily living (ADLs) (Hashimoto et al, 2017 ; Kawano et al, 2020 ; Tsai et al, 2021 ), duration of disease (Kawano et al, 2020 ), female gender, and low education level of the caregiver (Jhang et al, 2021 ) increased the caregiving burden. Worse cognitive function (Yu et al, 2015 ), using daily care services, and the male sex of the patient (Lucijanić et al, 2020 ) were also shown to increase the care burden in some cross-sectional articles.…”
Section: Introductionmentioning
confidence: 99%
“…Several regional studies have compared the burden of caregivers between different types of dementia (Yeager et al, 2010 ; D'Onofrio et al, 2015 ; Oliveira et al, 2015 ; Branger et al, 2018 ; Liu et al, 2018 ; Kawano et al, 2020 ), and the results of these studies were obscure. Two Asian studies conducted in Japan and China mentioned that caregivers taking care of subjects with Lewy body dementia (LBD) or frontotemporal dementia (FTD) experienced more burden than those caring for patients with AD dementia (Liu et al, 2018 ; Kawano et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Con icting ndings are also present in the literature [24,30]. In a comparative study, researchers found no signi cant difference in levels of burden reported by leukemia caregivers and cerebral palsy caregivers [24].…”
Section: Introductionmentioning
confidence: 89%